An industrial perspective on counter anions in gold catalysis: underestimated with respect to “Ligand effects” - Schießl, Jasmin; Schulmeister, Jürgen; Doppiu, Angelino; Wörner, Eileen; Rudolph, Matthias; Karch, Ralf; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2018)
The conversion of a variety of well-known test reactions, representing the key reactivity patterns of gold catalysis, were analyzed by GC and 1H NMR. The study is focused on establishing of a strategical approach for the consideration of ligand influence and counter anion influence during the catalyst optimization including an industrial perspective. The study shows a dominance of the counter anion, a dominance which up to now has been neglected in most of the routine screenings. In addition, a drastic substrate-dependency became obvious, even a marginal variation of the substrate already could strongly effect the catalytic activity and change the optimal counter anion or ligand. Based on the collected data a strategic concept for an efficient screening for a specific substrate is introduced, this concept can serve as an important guideline for catalyst optimization in homogeneous gold catalysis.